Rebalancing the rhetoric: A normative analysis of enforcement in street homelessness policy. (February 2021) - Johnsen, Sarah; Watts, Beth; Fitzpatrick, Suzanne
Street homelessness policies often provoke great intensity of feeling, especially when they include elements of force. This paper considers the moral case stakeholders present for and against enforcement in street homelessness policies via a series of philosophically informed normative 'lenses', including paternalist, utilitarian, rights-based, contractualist, mutualist and social justice perspectives. Drawing on in-depth qualitative research in six UK cities, it highlights the disparity between the condemnatory portrayals of enforcement dominant in academic and media discourses, and the more complex and/or ambivalent views held by practitioners and homeless people 'on the ground'. It concludes that an analytical framework that pays systematic attention to this span of normative lenses can facilitate more constructive, even if still 'difficult', conversations about policy interventions in this exceptionally sensitive area.